Exploring cross-taxon congruence between carabid beetles (Coleoptera: Carabidae) and vascular plants in sites invaded by Ailanthus altissima versus non-invaded sites: The explicative power of biotic and abiotic factors. (August 2019) - Uboni, Costanza; Tordoni, Enrico; Brandmayr, Pietro; Battistella, Silvia; Bragato, Gilberto; Castello, Miris; Colombetta, Giorgio; Poldini, Livio; Bacaro, Giovanni
Highlights: Plants species can be considered a surrogate taxon for carabid beetles. Cross-taxon congruence follows the gradient of vegetation in both stages. Gradient of vegetation and the native vegetation structure influence carabid beetles. Ailanthus altissima promotes anthropic and disturbed carabid beetles species. Abstract: Ailanthus altissima is one of the most global widespread invasive alien species and its effect as habitat transformer requires detailed investigations. In particular, its invasion in natural ecosystems and its effect on local fauna should be evaluated and described. With this purpose, the identification of surrogate taxa would be an important tool in order to define the impact of this invader on different habitats. Here, we evaluated cross-taxon congruence to quantify the strength of plant species composition in predicting multivariate patterns in carabid beetle assemblages, based on data from 20 sites divided in invaded and non-invaded habitats located in the Karst area, North-east Italy. We considered the habitat type (representing vegetation stages from grassland to forest) in order to evaluate the impact of A. altissima on carabid beetles along the vegetation succession. We found 28 carabid beetles and 173 plant species. Our analyses showed that plant species composition had a valuable predictive accuracy, based on the interplay among environmental variables, soil parameters and vegetation structure. Native vegetation and habitat type were the most important factors influencing carabid beetles and plant species composition. Furthermore, 33% of the total explained variation of carabid beetles assemblages (variance partition based on RDA analysis) was due to the independent effect of environment. We proved that cross-taxon congruence between carabid beetles and plants along the successional gradient of vegetation (habitat type). In particular, we attested that both communities present more species differentiation among non-invaded vegetation; in addition, in plots were A. altissima was present, anthropic and disturbed plants and carabid beetles species were prevalent. As a conclusion, plants can be effectively used as a surrogate taxon in the evaluation of the effect of A. altissima invasion in the Karst area.